The Level of Awareness and the Extent of Violation on the Implementation of Anti-Covid-19 Ordinance of 2020 in Dipolog City, Philippines - Mary Melmar G. Teves; Eljay J. Barbaso; Christialyn M. Galabin; Mariel L. Atab (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2023)
This study determined the level of awareness of the implementation and the extent of violation of the Anti-Covid-19 Ordinance of 2020 in Dipolog City, Philippines. It utilized the quantitative descriptive-survey method employing a validated research questionnaire as its principal tool in gathering data. The respondents were randomly selected residents from the different communities within the city. The gathered data were treated statistically using frequency counting, percentage computation, weighted mean, and Chi-Square test. The findings revealed that respondents were “Much Aware” of the implementation but the volume or the extent of reported violations reached up to 989 individuals being apprehended and fined during the implementation. Among the types of violations committed, failure to observe social distancing ranks first. Further, it reveals a significant relationship between the level of awareness and the extent of violation of the COVID-19 ordinance. The study recommends stricter enforcement of the local order and extensive awareness campaigns for the prevention of large-scale disease transmission and diminution of quarantine protocol violations.